2016
DOI: 10.1007/s00520-016-3415-8
|View full text |Cite
|
Sign up to set email alerts
|

Lost and stranded: the experience of younger adults with advanced cancer

Abstract: Advanced cancer in younger adults was perceived by them as isolating and as interfering with age-appropriate developmental tasks. Creative and flexible psychosocial support programs are needed to engage this population with limited expected survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 29 publications
3
59
1
Order By: Relevance
“…99,100 A Canadian interview study among AYAs aged 18 to 35 years with advanced cancer showed that patients experience their diagnosis as isolating (eg, feeling misunderstood or alienated) and unexpected (eg, cancer is a disease of older adults) and feel forcefully removed from the normal life trajectory. 101 In an American interview study, AYAs (20-40 years) reported anticipatory grief over their lives that have not yet been lived, 102 a psychological state that may be difficult for AYAs to process; they may be reluctant to face the irreversibility and progression of their disease. 102 This may lead to delays in the receipt of appropriate palliative and end-of-life care.…”
Section: End-of-life Challengesmentioning
confidence: 99%
“…99,100 A Canadian interview study among AYAs aged 18 to 35 years with advanced cancer showed that patients experience their diagnosis as isolating (eg, feeling misunderstood or alienated) and unexpected (eg, cancer is a disease of older adults) and feel forcefully removed from the normal life trajectory. 101 In an American interview study, AYAs (20-40 years) reported anticipatory grief over their lives that have not yet been lived, 102 a psychological state that may be difficult for AYAs to process; they may be reluctant to face the irreversibility and progression of their disease. 102 This may lead to delays in the receipt of appropriate palliative and end-of-life care.…”
Section: End-of-life Challengesmentioning
confidence: 99%
“…AYA with terminal and life-threatening illnesses may be extre-mely conscious of losing out on the adulthood their peers are approaching and never being able to achieve adult status, independence, and autonomy themselves (Davies et al, 2015;Greydanus, 2016). AYA who receive a terminal diagnosis have to grieve the loss of the future they have envisioned for themselves, as well as the future that friends and families expect for them (Knox et al, 2017). Common rite of passage milestones for AYA, such as going away to college, often are unobtainable for AYA with a life-threatening or terminal illness, yet the youth watch their healthy peers reaching these milestones knowing they cannot (Knox et al, 2017).…”
Section: Adjusted Developmental Tasks and Identity Formationmentioning
confidence: 99%
“…AYA who receive a terminal diagnosis have to grieve the loss of the future they have envisioned for themselves, as well as the future that friends and families expect for them (Knox et al, 2017). Common rite of passage milestones for AYA, such as going away to college, often are unobtainable for AYA with a life-threatening or terminal illness, yet the youth watch their healthy peers reaching these milestones knowing they cannot (Knox et al, 2017).…”
Section: Adjusted Developmental Tasks and Identity Formationmentioning
confidence: 99%
See 2 more Smart Citations